(untitled) (Mongolian Journal of Agricultural Sciences, 2024)
Genetic diversity of the mitochondrial Cytochrome Oxidase I gene in the Mongolian Old-World Swallowtail Butterfly from the beginning of Yeru River in Mandal Sum of Selenge Province, Natural Park of Khuvsgul Province, Dadal and Numrug Sum of Khentii Province, Ikh Nart Nature Reserve of Dornogovi Province were studied. The mitochondrial COI gene sequencing results showed 22 haplotypes with 84,6% variability and 36 sites with nucleotide substitution mutation and relative high nucleotide diversity (π=0,010225). There were detected 70 transition and 37 transversion mutation in total 107 mutation. Tajima’s D of the comparison an observed nucleotide diversity against the expected nucleotide diversity was -1,9039 indicating selectively neutral diversity. Comparison of interspecies and intraspecies genetic relationships of Old-World Swallowtail Butterfly by constructing a phylogenetic tree. The Mongolian population of the Old-World Swallowtail Butterfly was divided into 5 subpopulations with the same origin, geographical location and mitochondrial COI gene nucleotide diversity.